Women as leaders of higher education institutions: a British–German comparison. Issue 5 (3rd May 2016) - Read, Barbara; Kehm, Barbara M.
Abstract : Across the vast majority of countries women are a significant minority in senior academic positions, and as of 2013 only 17% of vice chancellors (VCs) of UK universities and 12% of German Universities were women. This paper discusses findings from a study consisting of interviews with eight female VCs of British and German higher education institutions. The paper takes a feminist poststructuralist approach to look at the ways in which characteristics of 'ideal' leaders in academia are discursively produced in a myriad of gendered ways, and looks at the influence of dominant academic cultures, status of institutions and national policy landscapes. From an analysis of the findings we argue that in addition to increasing the numerical proportion of women leaders in academia, work also crucially needs to be done to challenge academic cultural practices and dominant gendered conceptualisations of the 'leader'.